CHEMICAL SOIL STABILIZATION OF THE BANKS OF RIVER GHAGHARA - Kumar, Ashwani; Rawat, Anupam; Sachan, A (MATTER: International Journal of Science and Technology, 2017)
In this paper, fly-ash is used for the stabilization of the soil along the banks of river Ghaghara to prevent soil erosion that is caused by the flood. The sample from the site was obtained and different index properties test were performed. According to the optimum moisture calculated, the percentage of moisture content for the soil fly-ash mixture is taken as 25%. Three samples with fly-ash percentage viz. 10%, 15%, 20% are prepared and further direct shear test is performed. It can be seen that the 15% fly ash-Soil sample is found to be appropriate for preventing the lateral erosion as the shear strength of the 15% fly-ash mixture is greater than the critical shear strength of the soil. Thus the use of fly ash can be effective in improving the index properties of soil present at the site.